2018
DOI: 10.1037/pag0000248
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between subjective well-being and mortality within discordant twin pairs from two independent samples.

Abstract: Prior research has shown robust associations between greater subjective well-being (SWB) and reduced mortality. Whether this observed association is causal in nature or due instead to confounding genetic or environmental factors affecting both SWB and mortality is not well understood. We used a combined sample of 6,802 twins drawn from two cohorts: the Longitudinal Study of Middle-Aged Danish Twins (MADT; N = 2,815, baseline age between 45 and 69 years, M = 56.8, SD = 6.4) and the Longitudinal Study of Aging D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In addition, given the heritability of both SWB and lifespan [ 61 ], researchers suspected that some genetic factors may contribute to the association between SWB and survival. However, one study in Danish populations adopted a twin design to deal with the potential confounding effects of genes, and their findings indicated that SWB was associated with mortality independent of genetic factors [ 62 ]. More investigations from other populations are needed to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given the heritability of both SWB and lifespan [ 61 ], researchers suspected that some genetic factors may contribute to the association between SWB and survival. However, one study in Danish populations adopted a twin design to deal with the potential confounding effects of genes, and their findings indicated that SWB was associated with mortality independent of genetic factors [ 62 ]. More investigations from other populations are needed to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Results of a principal components analysis with two components, including standardised loadings for each wellbeing outcome, Eigenvalues, and proportion of variance explained................................................................................................................................... Table 3. Means and standard deviations of each TwIVI higher-order value for the total sample (Warr & Nielsen, 2018), and longevity (Saunders, Elkins, Christensen, & McGue, 2018). As such, developing strategies to increase wellbeing can have a far-reaching positive impact on individuals and society.…”
mentioning
confidence: 99%